Sistem Klasifikasi dalam Pemutaran Film: Studi Kasus Klasifikasi Film di Kinoki - Anshari, Irham Nur (Jurnal Ilmu Sosial dan Ilmu Politik, 2014)
This article concerns with the background, implementation, public acceptance and evaluation of the application of classification system as film regulation by Kinoki, an alternative screening space in Yogyakarta (2005-2011). The research adopted in this article is case studies. From the studies it is seen that the implementation of classification system at Kinoki is an effort to protect film viewers, while the application itself is more as a guideline for the viewers, yet so far public awareness and acceptance to this system is limited.